1998
DOI: 10.1016/s0750-7658(00)80006-4
|View full text |Cite
|
Sign up to set email alerts
|

Les cholinestérases

Abstract: Butyrylcholinesterase must be differentiated from acetylcholinesterase, which cannot hydrolyse succinylcholine. The physiological action of butyrylcholinesterase remains unknown, although it can hydrolyse many drugs. Excluding genetical mutations, several physiopathological situations alter butyryl-cholinesterase activity. Butyrylcholinesterase activity assessment does not allow the diagnosis of genetic variants. Whatever the origin, only deficits of more than 50% modify significantly the metabolism of succiny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 147 publications
0
1
0
Order By: Relevance
“…Although the primary purpose of this paper was to develop a NEST biosensor, we found that the approach could also be extended to measure the activities of other esterases involved in neural processes, including acetylcholinesterase (AChE) and butyrylcholinesterase (BChE). AChE, also known as true cholinesterase, is found in neural synapses and erythrocytes. BChE, also known as pseudocholinesterase, is found in the blood plasma. , Although both of these enzymes are capable of hydrolyzing the neurotransmitter acetylcholine into choline and acetic acid, a reaction necessary to turn off acetylcholine's neuroactive effects, they differ in their respective reactivities toward substrates. AChE preferentially hydrolyzes acetylcholine, whereas BChE preferentially hydrolyzes butyrylcholine.…”
mentioning
confidence: 99%
“…Although the primary purpose of this paper was to develop a NEST biosensor, we found that the approach could also be extended to measure the activities of other esterases involved in neural processes, including acetylcholinesterase (AChE) and butyrylcholinesterase (BChE). AChE, also known as true cholinesterase, is found in neural synapses and erythrocytes. BChE, also known as pseudocholinesterase, is found in the blood plasma. , Although both of these enzymes are capable of hydrolyzing the neurotransmitter acetylcholine into choline and acetic acid, a reaction necessary to turn off acetylcholine's neuroactive effects, they differ in their respective reactivities toward substrates. AChE preferentially hydrolyzes acetylcholine, whereas BChE preferentially hydrolyzes butyrylcholine.…”
mentioning
confidence: 99%